Advances in Computing Science ASIAN 2000 : 6th Asian Computing Science Conference Penang, Malaysia, November 25 27, 2000 Proceedings - Jifeng, He; Sato, Masahiko (Lecture notes in computer science ;, 2000)
This book constitutes the refereed proceedings of the 6th Asian Computing Science Conference, ASIAN 2000, held in Penang, Malaysia in November 2000. The 18 revised full papers presented were carefully reviewed and selected from a total of 61 submissions. The papers presented cover various topics in computer science and its applications, with a certain focus on networking and network performance and on programming logics and program semantics.